Comportamiento organizacional y metodologías ágiles en una entidad aseguradora, sede San Isidro (Lima- Perú), 2022 - Reyes Freitas, Rodrigo (2024)
Agile methodologies make possible and encourage change in companies, as today, companies that resist change are doomed to fail. Therefore, the objective of this work is to demonstrate that there is a direct and significant relationship between organizational behavior and agile methodologies in an insurance company located in San Isidro. The research was correlational, with a quantitative approach and a non-experimental design. The convenience sample consisted of 30 employees, who were asked to complete a Likert-type questionnaire with a scale from 1 to 5. It was possible to conclude that a direct and significant relationship exists between organizational behavior and agile methodologies, as well as a strong and positive correlation between them, with a Spearman’s coefficient of 0.8650.